Processing and characterization of highly oriented fibres of biodegradable nanocomposites. (1st September 2015) - La Mantia, F.P.; Mistretta, M.C.; Scaffaro, R.; Botta, L.; Ceraulo, M.
Abstract: Biodegradable polymeric materials are becoming day by day ever more important in packaging, agriculture, single-use cutleries and other large consumer applications. The major part of those materials is used under the form of film, i.e. subjected to elongational flow, but the main problem is that they often offer poor mechanical properties. Adding nanofillers, like Multi Walled Carbon Nanotubes (MWCNTs) may solve this problem but only if there is a full control of their orientation inside the material. Aim of this work is to investigate the processing-properties-morphology relationships for a system prepared under elongation flow of MaterBi and commercial MWCNTs. The materials were characterized both in shear and non-isothermal elongational flow and mechanical tests have been done on hot and cold drawn fibres. The morphology has been investigated by TEM. The shear viscosity increases dramatically in the presence of the MWCNTs, and the Cox–Merz relation does not hold. The mechanical properties of the hot stretched fibres strongly increase with the draw ratio but the increase is larger for the filled fibres because of the orientation of the MWCNTs. This is not true for the cold drawing because the very low mobility of the MWCNTs hinders their further orientation and the final properties seem driven by the matrix.